Leben im österlichen Vertrauen - Gottfried Bitter (Jesuit University Ignatianum in Krakow, 2017)
Many contemporary societies are experiencing deep cultural transformations. Until recently, discovering values and preserving them in social and private life was an integral part of tradition passed on from generation to generation. Today, this task is left to the individual. It also refers to the sphere of religion. Nowadays, everybody has to build his own world of religious images. Functioning well until recently, traditional forms of passing on the faith collapsed to a large degree. Everybody has to settle in the world of religion, in a way, under his own steam, which is the reason for miscellaneous "religiousnesses" and "christianities" emerging. In this context, the answer to the question about the specificity of Christianity, about Christian identity, becomes an inevitable necessity. Explaining the idea of Christianity, its peculiarity, has become the necessity for the Christians themselves, for Christian communities and churches, but also for non-Christians. The author of this article makes an attempt to show that the question about Christian identity is one of the oldest questions asked by Christian tradition. Already St. Paul provides the model answer (1 Cor 15, 3a-5). Also, the twentieth-century theologians face this question and try to reply to it according to their times (cf. R. Guardini, K. Rahner). In the end, the author himself makes a bold attempt to present his own concise formula of Christian identity (Life in paschal trust), in order to encourage others to seek their own formulas based on a sound foundation of Judeo- Christian tradition as well as their own Christian traditions. In this new way, individual autonomy in the sphere of religiousness and Christian identity may interweave and complement one another in the concrete way of life of each Christian.